Genome-wide characterization and comparative expression profiling of dual-specificity phosphatase genes in yellow catfish (Pelteobagrus fulvidraco) after infection with exogenous Aeromonas hydrophila - Guo, Shengtao; Zeng, Mengsha; Zhang, Chenhao; Fan, Yuxin; Ran, Miling; Song, Zhaobin (Frontiers in Immunology, 2024)
Introduction Dual-specificity phosphatases (DUSPs) are crucial regulators in many mammals, managing dephosphorylation and inactivation of mitogen-activated protein kinases (MAPKs) and playing essential roles in immune responses. However, their presence and functions in teleosts, like the yellow catfish (Pelteobagrus fulvidraco), remain unexplored. Methods In this study, eight pfDusp genes (pfDusp1-7 and pfDusp10) were identified in yellow catfish. We characterized their molecular features, conserved protein sequences, and chromosomal localization through genome-wide analyses, and we examined their expression patterns in immune responses. Results Our findings reveal two conserved motifs, Leu-Phe-Leu-Gly and Ala-Tyr-Leu-Met, within the DSPc domain of DUSP proteins. The genes were mapped across seven chromosomes without evidence of duplication. Comparative analysis showed high conservation of Dusp genes across vertebrates, with evolutionary analysis suggesting Dusp3 as a potential intermediate form. Dusp transcripts were significantly upregulated in the kidney post-A. hydrophila infection. Discussion These results suggest the involvement of Dusp genes in the immune response of yellow catfish to bacterial pathogens, providing insights into their evolutionary significance and potential applications in aquaculture and molecular breeding.